Substance use risk screening and associated factors among Costa Rican secondary students: a nationally representative analysis - Lopez-Soto, Andrea; Ramirez, Esmeralda; Cordoba, Jeancarlo; Montero-Zamora, Pablo (Frontiers in Public Health, 2025)
BackgroundAdolescent substance use (SU) is a significant public health concern in Latin America, however, representative data to guide prevention efforts remain limited. This study examined SU risk and potential associated factors among Costa Rican secondary students using the CRAFFT 2.1 screening tool.MethodsData were drawn from the 2021 VI National Survey on Psychoactive Substance Use in the Secondary School Population, a nationally representative sample of 3,524 students (weighted N ≈ 354,330). Based on CRAFFT scores, students were classified into low-, medium-, and high-risk SU groups. Multinomial logistic regression analyses assessed associations between SU risk levels and sociodemographic characteristics, SU within the family, sexual activity under SU, and exposure to violence.ResultsOverall, 64.7% of students were classified as low-risk, 26.6% medium-risk, and 8.7% high-risk. Older age, substance use by family members (i.e., smoking and illicit drug use), sexual activity under SU, and exposure to psychological and sexual violence were all associated with increased odds of classification into the high-risk group. Sexual activity under SU was strongly associated with membership in the high-risk group compared to both low- and medium-risk groups.ConclusionThis study is the first to apply the CRAFFT tool to a nationally representative sample of Costa Rican adolescents, providing critical insights for prevention initiatives in Latin America. Findings emphasize the need for universal multi-level prevention interventions to delay SU initiation and promote prosocial environments that support healthy youth development, ultimately reducing the burden of SU among Costa Rican adolescents.